Particular Matter of Motor Vehicle Exposure and High-Fat Diet Effects on Kidney Histopathology, Creatinine, and Malondialdehyde (MDA) Levels in Wistar Rats - Veni, Rizka; Prasetyo, Awal; Muniroh, Muflihatul (Research Centre of Inorganic Materials and Complexs, 2021)
This study aims to analyze the effect of combination of motor vehicle particular matter exposure and high-fat diet in kidney histopathology, creatinine levels, and MDA levels in Wistar rats. This study used a posttest-only control group design. Eighteen healthy male Wistar rats were divided into three groups. The intervention groups received motor vehicle fume exposure for 100 s with normal diet (X1) or high-fat diet (X2), and the control group received no exposure (C). Data analysis was processed with a SPSS 25.0 computer program by using the one-way ANOVA test followed by post hoc LSD. The degree of kidney histopathological damage showed significant differences between the X1 and X2 groups when compared with the control group (p < 0.05). The results of the creatinine level examination found a significant difference between the X2 and C groups (p < 0.05) and the treatment groups X1 and X2 (p < 0.05). The results of kidney MDA level examination showed a significant difference between the treatment groups (X1 and X2) and the control group (p < 0.05). The combination of particular matter of motor vehicle fumes exposure and high-fat diet could induce kidney damage through histopathological change and increased creatinine levels and kidney MDA levels in Wistar rats.